Membangun Karakter Sempurna Berdasarkan Matius 5:48 Jemaat Gereja Suara Kebenaran Injil di Medan - Rinto Francius Sirait (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
The aim of this study is to know and understand holistically the things that Jesus taught about perfect character in Matthew 5:48, so that with this understanding, all workers or servants of God and the congregation of GSKI Medan City can learn and live what Jesus taught related to perfect character. The research method used in this study is a Qualitative method with a phenomenological approach. The data sources used in this study are semi-structured interview guides and field notes. The data analysis technique used in this study involves several steps, namely bracketing, horizontalization, phenomenological reduction, and synthesis of essential meaning. The results of the study show that: The congregation and servants of God GSKI in Medan City understand the teachings of Matthew 5:48 as a call to perfection exemplified by the Father in heaven; The congregation and servants of God GSKI in Medan City identified several key attributes in achieving perfect character which include high moral quality, holiness, commitment to following God's will, and growth in faith through deepening the Word and fellowship; The congregation GSKI in Medan City faces several major challenges in building perfect character according to the teachings of Matthew 5:48, such as limitations in understanding the teachings of the Bible and incomplete doctrines, worldly influences and attachment to worldly pleasures, and the lack of consistent role models from church leaders; An effective teaching model for building perfect character based on Matthew 5:48 in the context of the congregation GSKI in Medan City consists of: a structured teaching approach, practical and contextual application, as well as role models and leadership